2009
DOI: 10.1016/j.jcrs.2009.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal corneal ring segment implantation for high astigmatism after penetrating keratoplasty

Abstract: PURPOSE: To evaluate the safety and efficacy of intracorneal ring segments (ICRS) for high astigmatism after penetrating keratoplasty (PKP). SETTING:METHODS: This retrospective noncomparative study comprised eyes with high post-PKP astigmatism (>4.00 diopters [D]), contact lens intolerance, and a minimum follow-up of 24 months who had ICRS (Kerarings) implantation by mechanical stromal dissection. Corrected distance visual acuity (CDVA), refractive astigmatism, spherical equivalent (SE), surgically induced ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 31 publications
5
38
0
25
Order By: Relevance
“…According to Coskunseven et al, eyes with thin corneal grafts and recurrent keratoconus are unsuitable for laser refractive corrections because of the possibility of postoperative complications. In addition, Arriola-Villalobos et al, 5 in a series of 9 patients, found that ICRS implantation improved the CDVA in all eyes and decreased the topographic mean, minimum, and maximum K values. They conclude that ICRS implantation might be a good surgical choice to correct high astigmatism after PKP and yields good visual, refractive, and topographic outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…According to Coskunseven et al, eyes with thin corneal grafts and recurrent keratoconus are unsuitable for laser refractive corrections because of the possibility of postoperative complications. In addition, Arriola-Villalobos et al, 5 in a series of 9 patients, found that ICRS implantation improved the CDVA in all eyes and decreased the topographic mean, minimum, and maximum K values. They conclude that ICRS implantation might be a good surgical choice to correct high astigmatism after PKP and yields good visual, refractive, and topographic outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…We proceeded as Arriola-Villalobos et al 5 suggest; that is, we waited at least 2 years after corneal transplantation and a minimum of 6 months after suture removal to avoid damaging the interface by the traction generated by the dissectors used during surgery in the manual technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 However, several complications were encountered during and after Kerarings implantation including small dehiscence of grafthost interface during stroma tunnel dissection, an inflammatory infiltrate around the segment immediately after operation, stromal channel vascularization leading to ring explantation and night halos. 34 …”
Section: Intrastromal Corneal Ring Segmentsmentioning
confidence: 99%
“…Moreover, ICRS implantation appears to reduce corneal curvature and topographic astigmatism, providing satisfactory visual results, but the effect of this reduction on refractive astigmatism is not significant. 3 It is also important to remember that ICRS nomograms are designed for keratoconus treatment, as recognized by the authors, and they are based on subjective empirical data, although the complex biomechanical alterations after ICRS implantation necessitate a more sophisticated mathematical model for analyzing the corneal ring effect. 4 This may represent a possible explanation for the low predictability of ICRS implantation in the surgical treatment of post-PKP astigmatism, at least to some extent.…”
Section: Other Cited Materialsmentioning
confidence: 99%